GAYA KEPEMIMPINAN DARI ATAS KE BAWAH - Darto Sachius (Jurnal Teologi Biblika, 2020)
This study will look for Dari atas ke bawah leadership values ​​and find the meaning of why a leader prefers to use this style rather than using another leadership style that is more effective? This research uses qualitative, not experimental, methods. This method is used for social and humanities research and can also be used in research or theological studies. From the results of the discussion above, it is found five values ​​of the first Dari atas ke bawah leadership: Top down leadership style is already entrenched. These two leadership styles are most commonly practiced in every third generation. The third leadership style is the easiest to implement because this style of a leader only commands the people under him. The four Leadership styles that are natural under one person is born with Adam's sin with a dominant nature over others. This is a dangerous trend. These five top-down leadership styles are leadership styles that damage relationships with one another because top-down styles pursue results more than humans so humans are sacrificed for certain results.